Estimate the Concentrations of Some Heavy Metals in Industrial Wastewater in Al-Dora Oil Refinery - Hawraa G. Auied; Saadiyah A. Dhahir; Maitham A. Sultan (Journal of Engineering)
Industrial wastewater is discharged in large quantities into water bodies, and different treatment processes are employed to reduce pollutant levels. This study quantifies copper, iron, cadmium, cobalt, lead, and nickel levels in industrial wastewater samples at Al-Dora refinery. Results showed variations before and after treatment, with physical and chemical tests conducted in summer and winter. The measured values ​​were (pH, T, Turbidity, EC, TSS, TDS ), respectively (8.23, 34.8 °C, 60.88 NTU, 2883 ms/cm, 575 mg/L, 1441 mg/L) in summer, while in the winter it was (7.516, 28.6 °C, 100.6 NTU, 1147 ms/cm, 780 mg/L, 569.8 mg/L), respectively. Heavy metals were measured and showed a slight decrease during the treatment units, nevertheless, they continue to be among the environmental determinants of the Iraqi river maintenance system (1967). The measured elements were (Cu, Fe, Cd, Co, Pb, and Ni), and their concentrations in the treated water and discharged to the river were (0.064, 0.020, 0.109, 0.031, 0.029, 0.092) mg/L, respectively, in the winter.  While in summer, their concentrations were  (0.017, 0.018, 0.0105, 0.017, 0.138, 0.078) mg/L, respectively. The values of pollutant concentrations were a key environmental factor in the maintenance of Iraqi rivers, as the treatment plant effectively reduced or removed these pollutants from the water before discharging it into the river, without impacting water quality.